Can Government Intervention Make Firms More Investment-Ready? - Cusolito, Ana Paula (World Bank, Washington, DC, 2018)
Innovative start-ups and SMEs in developing and transition countries often have good ideas, but may not have these ideas fine-tuned to the stage where they can attract outside funding. This is the case in the Western Balkans, where there is a perceived lack of investment readiness of innovative start-ups to be in a position where they can compete for, and take on, outside equity.Investment Readiness Programs are a relatively new intervention that are intended to provide a comprehensive approach to overcoming the constraints to firms receiving outside investment through a mix of individualized training, mentoring and coaching, at an intensity that is sufficient to make firms more investment-ready, while maintaining a cost that is low enough to be scalable to large numbers of firms. These programs have now been used in the U.S. by the National Science Foundation, and by several government agencies in Europe (e.g. The UK Government’s Small Business Service and Enterprise Ireland), along with pilot programs in Romania and Malaysia. However, to date there is no causal evidence as to their effectiveness.